2019
DOI: 10.1051/0004-6361/201935528
|View full text |Cite
|
Sign up to set email alerts
|

The environment of supernova remnant VRO 42.05.01 as probed with IRAM 30m molecular line observations

Abstract: Context. The environment of supernova remnants (SNRs) is a key factor in their evolution, particularly at later stages of their existence. Mixed-morphology (MM) SNRs have a peculiar centre-filled X-ray shape that remains enigmatic. It is often assumed that they evolve in very dense environments, and that the X-ray morphology is due to interactions between the SNRs and their surroundings. Aims. We aim to determine whether VRO 42.05.01 is embedded in, and interacting with, a dense molecular environment. We also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 37 publications
(61 reference statements)
5
26
0
Order By: Relevance
“…Therefore, we suggest that the expanding structure and the velocity gradient of the molecular gas could be due to the progenitor wind of G106.3+2.7. We note that similar structures due to progenitor winds have also been found in a few other SNRs, such as Tycho (Zhou et al 2016;Chen et al 2017), N132D (Sano et al 2020), and VRO 42.05.01 (Arias et al 2019).…”
Section: Molecular Line Profilessupporting
confidence: 83%
“…Therefore, we suggest that the expanding structure and the velocity gradient of the molecular gas could be due to the progenitor wind of G106.3+2.7. We note that similar structures due to progenitor winds have also been found in a few other SNRs, such as Tycho (Zhou et al 2016;Chen et al 2017), N132D (Sano et al 2020), and VRO 42.05.01 (Arias et al 2019).…”
Section: Molecular Line Profilessupporting
confidence: 83%
“…However, the wind properties are determined by the natural size of VRO, which in turn is determined by the distance of the object. Given that VRO distance is not well defined (Landecker et al, 1989;Arias et al, 2019a), the properties of the anisotropic wind that shaped the cavity around VRO, and thus the nature of the progenitor star, are up to date, not well constrained. A sequence of papers relevant to VRO will be published soon (VRO's optical observations; Boumis et al (2019) and VRO's 3D morphokinematical modeling; Derlopa et al 2019) that are expected to limit the parameter space of the remnant's physical quantities and consequently provide vital insights on the unknown nature of VRO 42.05.01.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the interaction of the SNR with the surrounding Mach cone formed the triangular-shaped 'wing'. However, recent observations of VRO and its environment did not reveal any physical proof of an interaction between the remnant and a non-homogeneous surrounding medium (Arias et al, 2019a). This fact in combination with the lack of any detailed modeling of VRO retains its origin largely unknown.…”
mentioning
confidence: 91%
“…That means that the "shell" goes inwards the page, while the "hat" component goes outwards from the page. Concerning the "wing" component, the model showed that its northern part is bent with respect to its eastern counterpart, implying a possible interaction with a denser ambient medium at this part of the remnant (see also Arias et al 2019b). In addition, a part of the "wing" penetrates the central region of the "shell" at its front side (see Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The part of the remnant that evolved into the denser region created the "shell" component, while the rest diffused into a hotter and tenuous medium and shaped the "wing" component. However, according to the recent results presented by Arias et al (2019b), there is no physical proof of an interaction of the remnant with the surrounding molecular clouds and they attributed the almost triangular shape of the "wing" to a Mach cone cavity which was created by a supersonically moving progenitor star and was filled out by the SN ejecta. Finally, Chiotellis et al (2019) modeled the observed morphology of VRO with 2D hydrodynamic simulations, suggesting that the remnant is currently interacting with the density wall of a wind bubble sculptured by the equatorial confined mass outflows of a supersonically moving progenitor star.…”
Section: Introductionmentioning
confidence: 99%